Hepatic encephalopathy. Clinical case - Rafalska, Natalia (Journal of Education, Health and Sport, 2021)
Hepatic encephalopathy is a neuropsychiatric syndrome associated with abnormal liver function and portosystemic venous shunting. According to the West-Haven classification, depending on the degree of neurological disorders, there are minimal, I - IV stages of HE, which are characterized by a gradual progression of the disease. To date, the pathogenesis of HE is controversial.